An algorithm for joint optimization of dynamic routing and scheduling in time-sensitive networking - Yang ZHOU; Honglong CHEN; Lei ZHANG (物联网学报)
Time-sensitive networking (TSN) is a set of protocols developed by the IEEE TSN task group, aiming at achieving deterministic communications over Ethernet.As the implementation method of TSN traffic scheduling is not specified in the protocols, the routing and scheduling algorithm for TSN remains an open issue.The joint optimization problem of routing and scheduling in TSN for industrial applications was modeled, and then an online heuristic algorithm was proposed to deliver the routing and scheduling solution for dynamic traffics.The routing path was determined by optimizing both the transmission delay and network load factors, and the scheduling time was quickly conducted by twice clipping operations.Finally, a simulated TSN testbed was developed with NeSTiNg framework based on OMNeT.The simulation results show that the execution time of the proposed algorithm outperforms the baseline algorithms even with large scale of network size and network traffics.It shows that the proposed algorithm guarantees the real-time performance even in dynamically changing networks.